Sistem Informasi Pelayanan GMIT Tiberias Kupang Berbasis Mobile - Jimrio Vicky Stanley Benu; Alexander Setiawan; Djoni Haryadi Setiabudi (Jurnal Infra, 2021)
Currently, most church service information systems are still manual. In the GMIT Tiberias Kupang environment, the media used in delivering the service information to the congregation is still done conventionally, through reading and sharing of church news which can only be obtained on Sundays when the main service is held. Therefore, the delivery of information becomes less effective and efficient. Furthermore, during the Covid-19 pandemic, it allows the spread of the virus to the congregation through congregational newsletters, worship liturgies, and financial reports. Likewise, manual administrative and congregational data management activities can cause errors and increase operational costs.Along with the rapid development of information technology, it is possible to design the application of a church service information system that can optimize services and information systems at GMIT Tiberias Kupang by presenting various features that are able to answer the needs of the church community for both ministers and congregations, considering that currently almost all congregants or in every household at least one family member already has an android phone.The purpose of making this application is to optimize the service information system for the GMIT Tiberias Kupang congregation that is effective and efficient by using a mobile application. Application made for using Android Studio with Java and Firebase programming languages as databases and website creation for admins using HTML, CSS, and PHP programming languages. The results of this study indicate that the level of congregational satisfaction with the church service information system has increased significantly after using the GMIT Tiberias Kupang Mobile-Based Service Information System Application.